Wood use and kayak construction: Material selection from the perspective of carpentry - Walls, Matthew (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2012)
AbstractAlthough the natural availability and quality of wood is variable across the Arctic, there is great continuity in how it was traditionally used. This article considers the value of wood to Arctic peoples and the criteria that would distinguish the utility of different pieces. The topic is explored in the case of kayak construction, one of the most complex carpentry tasks that can be inferred from many archaeological sites. Numerous types of kayaks were built in several periods by a variety of peoples using very different toolkits. Using both ethnographic and archaeological examples, it is shown that this technology everywhere shared several key stages of construction. Within these stages, specific carpentry tasks defined the criteria that all kayak builders used to select wood. By exploring the value of wood to Arctic peoples for carpentry, this article demonstrates the potential for understanding wood use through experimental archaeology.